Online Learning Interaction Patterns During the Covid-19 Pandemic: Prospective teachers’ Perceptions - Ismail Ismail; Agus Muliadi; Ni Nyoman Sri Putu Verawati (IKIP Mataram, 2022)
The intensity of the implementation of learning with the online system during the Covid-19 pandemic certainly has an impact on the learning process and the results that have been achieved. In the process of implementing it in a sustainable manner, it is necessary to evaluate, especially in the aspect of student perceptions as beneficiaries of the implementation of the online learning system during the Covid-19 pandemic. Specifically, this study aims to determine the perceptions of prospective teacher students about online learning interaction patterns during the Covid-19 pandemic. This study is an exploratory descriptive study involving 107 respondents, they are prospective-teachers at one of the private universities in Mataram City, Indonesia. The online questionnaires were filled out by considering accessibility, therefore the convenience sampling technique was used. Perceptions of prospective teacher were measured using a closed questionnaire instrument. Each prospective teacher responses are degraded based on a Likert scale. The questionnaire instrument is composed of 10 items of questions or statements, it contains aspects of online learning interactivity. Prior to application, the psychometric properties of the instrument must be met. The psychometric properties used are aspects of instrument validity. Before being applied, the questionnaire instrument was validated by experts, and the results of the instrument have been declared valid. Data analysis was carried out statistically. The differences in perception by employing the ANOVA test (p < 0.05). The findings of the study indicate that the perception of prospective teachers is 'sufficient' regarding online learning interactions during the Covid-19 pandemic. Aspects of the online learning experience for prospective teachers in each department showed that there was no significant difference in the perception of prospective teachers about online learning interactions during the covid-19 pandemic (significance of 0.213 > p, 0.05). The findings in this study can be the basis for improving the online learning process by universities, where this can be optimized so that in the future online learning services can be even better. As it is known that the online system is the only choice of the best learning mode during the Covid-19 pandemic. In addition, we see the online system as a learning trend that does not last a short time, but becomes a new direction of learning now and in the future.